Project-Based Learning in Elaborating Interactive Media Based on E-Modules for Prospective Physics Teachers - Ute, Nilawati; Halmuniati (Journal of Educational Technology Innovation and Applications, 2025)
This study aims to explore the implementation of the Project-Based Learning (PjBL) model in the development of interactive e-module-based learning media by prospective physics teachers. The research method used is qualitative descriptive research, with subjects being students of the Physics Education study program who are enrolled in the learning media course. The learning process follows the stages of PjBL, starting from problem identification, project planning, product development, to presentation and reflection. The results of the study show that the PjBL approach can enhance students' creativity, critical thinking skills, and technological abilities in designing interactive learning media relevant to the needs of physics education. In addition, the developed e-modules feature interactive elements that support deeper and more engaging conceptual understanding. In conclusion, PjBL is effective in equipping prospective physics teachers with the pedagogical and technological competencies needed in the era of digital learning.